2015
DOI: 10.4186/ej.2015.19.4.83
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading Feldspar by WHIMS and Flotation Techniques

Abstract: Large reserves of feldspar ores exist in the pegmatite veins at Ban Tak district, Tak province. The main impurities of these deposits are muscovite, biotite and garnet which resulted in high Fe-content that does not meet the raw materials specification for ceramic industry. Chemical compositions of the feldspar ores are 75.93 %SiO2, 14.34%Al2O3, 0.63% Fe2O3, 4.01%K2O and 4.34%Na2O with the fire test results of L= 63.10, a = 2.04 and b = 10.56. The typical specifications of the commercialised feldspar require %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A complete chemical analysis of the head sample was carried out using X-ray fluorescence (Xrf) technique; the results are shown in Table 1. The results showed that the feldspar sample is of low grade under market standards for the manufacturing of glass and ceramic/pottery grade feldspar specifications [14,19]. iron oxide contents (0.69%) should be reduced to <0.1% to be suitable for different industries.…”
Section: Sample Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete chemical analysis of the head sample was carried out using X-ray fluorescence (Xrf) technique; the results are shown in Table 1. The results showed that the feldspar sample is of low grade under market standards for the manufacturing of glass and ceramic/pottery grade feldspar specifications [14,19]. iron oxide contents (0.69%) should be reduced to <0.1% to be suitable for different industries.…”
Section: Sample Characterisationmentioning
confidence: 99%
“…feldspar is applied in glass manufacturing as a fluxing factor as well as a source of alkali (K 2 o & na 2 o), alumina (Al 2 o 3 ), and silica [11][12][13]. The standard specifications of the marketed feldspar require Sio 2 <70%, Al 2 o 3 >17%, fe 2 o 3 <0.1% with K 2 o and na 2 o both >5% [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some researches on feldspar ore show that some types of feldspar from various locations in various countries are further processed. This processing can use magnetic separator (wet and dry processes), flotation process (anion and cationic flotation), mixture of magnetic separator and froth flotation, biological and electrochemical processes, and leaching process by using acid medium [4]- [8]. Table 3.…”
Section: A Feldsparmentioning
confidence: 99%
“…The grade of the concentrate that is made after dry magnetic separation can be raised even more by using wet magnetic and flotation methods, which free up more mineral particles (Gougazeh, 2006;El-Rehiem and Abdel-Rahman, 2008). As a result, efficient separation of Fe-bearing minerals on a commercial scale and in an environmentally benign manner could be achieved (Saisinchai et al, 2015). A Turkish feldspar sample was processed in a rare earth roll magnetic separation to separate the colouring impurities (Gülsoy et al 2004, Gülsoy et al 2005.…”
Section: Introductionmentioning
confidence: 99%